The impact of employing insulation with variant thermal conductivity on the thermal performance of buildings in the extremely hot climate. (December 2019) - Khoukhi, Maatouk; Hassan, Ahmed; Abdelbaqi, Shaimaa
Abstract: This paper illustrates the impact of transient thermal conductivity of the insulation layer embedded in a typical residential building on cooling effect and energy performance. The test was performed applying expanded polystyrene (EPS), as an example of insulation material, in the extremely hot climate of UAE at different levels of densities, and three moisture content levels (10%, 20%, and 30%) compared to dry insulation material for Low density (LD) material. Thermal wall resistance was evaluated by applying a conjugate heat-transfer model based on enthalpy-based formulation. The thermal performance of the building incorporating expanded polystyrene with variable thermal conductivity was compared to non-variable thermal conductivity by quantifying the additional cooling demand and capacity due to the λ relationship with time using the e-quest as a building energy analysis tool. The results show that, when the λ value is modeled as a function of operating temperature, its effect on the temperature profile during daytime is significant. The LD expanded polystyrene insulation leads to the lowest heat resistance across the wall section. Applying different levels of moisture showed that 30% moisture content has the lowest heat resistance compared with 10% and 20%, resulting in the highest change of 6.5% and 8.9% in cooling demand and capacity, respectively.